Evaluation of Brand Equity and Resonance of Banking Services in India: An Empirical Application of Keller’s Brand Equity Model - Garg, Arunesh (Gyan Management Journal, 2013)
The study investigates Brand Resonance Model of customer-based brand equity in context of banking industry. Data have been collected from 640 customers of banks in the State of Punjab and the Union Territory of Chandigarh. The study has identified components of brand equity of banking services. It is revealed that brand resonance has very strong, positive and significant correlation with brand judgments, brand feelings and brand imagery. However, brand judgments and brand feelings are relatively strong predictors of brand resonance as compared to brand imagery and brand performance. The study concludes that though emotional and functional aspects of banking services cannot be separated, but banks should focus more on emotional concerns of the customers.